Speech Development Across Subgroups of Autistic Children: A Longitudinal Study. - Broome, Kate; McCabe, Patricia; Docking, Kimberley; Doble, Maree; Carrigg, Bronwyn (Journal of Autism & Developmental Disorders, 2023)
Subgroups of children with different speech profiles have been described however, little is known about the trajectories of speech development or stability of subgroups over time. This longitudinal study described both speech trajectories and subgroup stability of 22 autistic children, aged 2;0–6;11 years, over 12 months. Independent and relational speech analyses, vocabulary size and nonverbal communication were used in clustering. Results suggest varied speech trajectories, particularly for children with 'low language and low speech' at Time 1. Receptive vocabulary and consonant inventory at Time 1 may predict speech outcomes after 12 months. A small subgroup of children (n = 3) present with low expressive vocabulary and speech but higher receptive vocabulary and use of gestures. This unique profile remained stable.